A capacitated multi-product dynamic lot-sizing problem by considering expiration dates; A new approach - AL-E-HASHEM, S.M.J. MIRZAPOUR; SAZVAR, Z.; BABOLI, A.; REKIK, Y.; JOKAR, M. AKBARI (IFAC Proceedings Volumes, 2013)
Although managing and controlling the inventories of perishable products is progressively becoming more important, they are often neglected in lot-sizing research and modeling. This paper studies a new multi-product multi-period dynamic lot sizing problem, where the inventories of products are assumed to be expired at a pre-specified date. For this purpose we assume a retailer that purchases products in large quantities (lot size) from manufacturers, and then sells smaller quantities (or single units) to the consumer. So, the order quantities can be merely an integer multiplier of that product batch size. The retailer also owns a capacitated warehouse. In order to make decisions on “how much to order” and “when to order”, a novel mixed integer programming model is developed that minimizes total costs including the procurement cost, inventory holding cost, ordering, backordering and expiration costs subject to warehouse capacity. Furthermore, a numerical example is presented to demonstrate the applicability of the proposed model.